So we know that the pattern goes that i^3=-i and i^7 is also -i. So if you set them equal to each other, i^3=i^7 and then take the log to both sides you get:
3ln(i)=7ln(i)
And then you can simplify this down by dividing out the ln(i) to get 3=7. Obviously this isn't true, so what am I doing wrong?

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

|dw:1352847101536:dw|

http://www.wolframalpha.com/input/?i=ln(i)&t=crmtb01

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.